Effectiveness of education strategies in reducing needle stick injuries among nurses of private hospitals in Jordan - Khraisat, Firas Shehadeh Abdullah (2017)
Introduction: Needle stick injuries are “punctures of the skin with a needle”. Needle stick injuries cause severe consequences such as the transmission of blood borne diseases. Nurses are the most occupational group under the risk of acquiring a needle stick injury. In Jordan, a study revealed that 92% private hospital nurses have acquired at least one needle stick injury within the past 12 months (Hassan and Wahsheh, 2009). Another study in Jordan showed that 90% (46 out of 51) of the nurses working in private hospitals acquired at least one needle stick injury (Abozead et al., 2015). Objective: To develop, implement, and evaluate the effectiveness of educational module and strategies to reduce needle stick injuries among nurses of private hospitals in Jordan. Methodology: This study utilized a Randomized Control Trial design with four arms; three intervention groups and one control. All private hospitals were screened for inclusion eligibility, then simple random sampling was performed to select four hospitals, and then a total of 102 nurses were sampled inside each hospital using stratified random sampling with total of 408. Education was provided utilizing three strategies: Social Media, Audio-visual, and combined. Data were collected on three waves; baseline, three months, and six months after completing the interventions. Results: Significant difference in injury occurrences after three months found only between control group and combined intervention group (P= 0.002). After 6 months significant differences were found between control and social media groups (P= 0.032), control and audio-visual groups (P= 0.007), and control and combined groups (P<0.001). For the knowledge, attitudes, and practices, after 3 months the number of variables with significant differences between intervention and control groups was six (P<0.05), and increased to nine after 6 months (P<0.05). For the beliefs, at baseline only 3 variables out of 26 showed significant differences between study groups (NSI not preventable, P=0.04; Injection likelihood, P= .002; Any training/education, P= .04), but after 3 months the number of variables increased to five, and increased to eleven after 6 months (P<0.05). The results for risk factors of needle stick injuries were fatigue (P<0.001), lack of assistance (P= 0.001), emotional distress (P= .021), being rushed (P= .002), and Lack of skills (P= .001). The hierarchical regression for the prediction of changes in injury occurrence produced a model with four predictors after three months (P< .001), and six predictors after six months (P< .001). Conclusion: the newly developed education module and strategies are successful in significantly decreasing the occurrence of needle stick injuries in all three intervention groups. Changing nurses’ beliefs towards needle stick injuries and increasing their knowledge resulted in changing behaviors, which lead to decrease the occurrence of needle stick. Five risk factors were found to be significantly associated with needle stick injuries; fatigue, lack of assistance, emotional distress, being rushed, and Lack of skills. The reduction in injuries could be predicted by the intervention strategies, changes in knowledge, practices, attitudes, and beliefs.